Imaging of Neurotrauma in Acute and Chronic Settings - Mallon, Shane; Kwiecien, Jacek M.; Karis, John P. (Current Neuropharmacology, 2021)
Traumatic injuries of the brain and spinal cord are a significant source of mortality and long-term disability. A recent systematic study in a rat model of spinal cord injury (SCI) indicates severe, destructive, and very protracted inflammation as the key mechanism initiated by the massive injury involving the white matter. Although the severe inflammation is localized and counteracted by astrogliosis, it has a damaging effect on the blood vessels in the surrounding spinal cord, leading to persistent vasogenic edema. Evaluation of these injuries with imaging of the brain and spinal cord plays a crucial role in the acute trauma work-up, allowing clinicians to quickly identify abnormalities that require immediate medical or surgical intervention or to exclude them from the workup. Recently, anti-inflammatory agents have been shown to inhibit and accelerate the elimination of post-SCI inflammation in preclinical studies, and an exciting potential has arisen for the use of antiinflammatory drugs in clinical studies to achieve neuroprotection (i.e., inhibition of destruction caused by inflammation) and to inhibit vasogenic edema in SCI, traumatic brain injury, and stroke. In both subacute and chronic settings, imaging can guide therapy and provide important prognostic information. In this review, we discuss the imaging workup and evolving imaging findings of neurotrauma in the acute and chronic setting, including conventional and advanced imaging techniques. As neuroimaging is the primary mode of diagnostic analysis in neurotrauma, it is a critical component in future clinical trials evaluating neuroprotective therapies.
Keywords: traumatic axonal injury